How the activity of natural enemies changes the structure and metabolism of the nutritive tissue in galls? Evidence from the Palaeomystella oligophaga (Lepidoptera) -Macairea radula (Metastomataceae) system - Rezende, Uiara C.; Cardoso, João Custódio F.; Kuster, Vinícius C.; Gonçalves, Letícia A.; Oliveira, Denis C. (Protoplasma, 2019)
Insect-induced galls usually develop nutritional cells, which they induce and consume directly, and any metabolic modification of those cells may reflect changes of the insect’s own metabolism. The system Palaeomystella oligophaga (Lepidoptera) — Macairea radula (Melastomataceae) presents a series of natural enemies, including parasitoids and cecidophages that can function as a natural experiment, respectively removing the specific galling feeding stimulus and providing a nonspecific one. Considering that the process of induction and maintenance of gall tissues strictly depends on the constant specific stimulus of galling, question I:What kind of metabolic changes these different groups of natural enemies can promote in chemical and structural composition of these galls? II: How the specialized tissues are metabolically dependent on the constant specific stimulus of galling in latter stages of gall development? Galls without natural enemies, with parasitoids or cecidophages in larvae or pupae stages were analyzed through histochemistry and cytological profiles and all compared to galls in natural senescence state. The analysis revealed the accumulation of proteins and lipids in typical nutritive tissue and starch in the storage tissue, as well a high integrity of cellular organelles and membrane systems on galls with gallings in the larval stage. Both parasitoids and cecidophages stop galling feeding activities, which resulted in the paralysis of the stimulus that maintain the metabolism of gall tissues, leading to generalized collapse. We demonstrate that the development and metabolic maintenance of a typical nutritive tissue in these galls are completely dependent on constant larval stimulus.